Gut microbiota: an emerging target connecting polycystic ovarian syndrome and insulin resistance - Mei, Yufeng; Li, Wanzhen; Wang, Bingqi; Chen, Zhenni; Wu, Xinyi; Lin, Yingrui; Wang, Min (Frontiers in Cellular and Infection Microbiology, 2025)
Polycystic ovary syndrome (PCOS) is a highly heterogeneous metabolic disorder, with oligomenorrhea and hirsutism as patients’ primary complaints. Hyperinsulinemia is a crucial pathophysiological mechanism in the development of PCOS, with 50-70% of patients exhibiting insulin resistance (IR). This condition not only exacerbates ovulatory dysfunction but also leads to various adverse metabolic outcomes, such as dyslipidemia and diabetes, and increases the risk of cardiovascular events both before and after menopause. Gut microbiota is a microbial community within the host that possesses significant metabolic potential and is shaped by external environmental factors, the neuro-immune network, and metabolism. Recent studies have shown that gut microbiota dysbiosis is closely related to the development and progression of PCOS. Despite the growing recognition of the potential role of gut microbiota in the pathogenesis and treatment of PCOS, its clinical application remains in its infancy. Currently, most clinical guidelines and expert consensus still emphasize traditional therapeutic approaches, such as hormonal treatments, lifestyle modifications, and insulin sensitizers. However, accumulating evidence suggests that gut microbiota may influence the metabolic and reproductive health of PCOS patients through various mechanisms. Therefore, understanding the role of gut microbiota between PCOS and IR is essential. This review describes the changes in the gut microbiota of IR-PCOS patients, examines the potential mechanisms by which the gut microbiota contributes to IR in PCOS patients, and updates the evidence supporting the gut microbiota as a potential metabolic regulatory target in IR-PCOS. In summary, gut microbiota dysbiosis may be involved in the development and progression of IR in PCOS patients, and improving gut microbiota may offer metabolic stability benefits.